LEXICON ANALYSIS OF FLORA AND FAUNA IN THE NOVEL “AL-AJNIHAH AL-MUTAKASSIRAH” BY KAHLIL GIBRAN BASED ON THE ECOLINGUISTICS PERSPECTIVE - Ghina Aulia Nurinsani; Abdul Basid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The lexicon of flora and fauna in literary works is an interesting topic for study. It can be found by researchers in the novel “Al-Ajnihah al-Mutakassirah” by Kahlil Gibran as a characteristic of the author in describing an event with more beautiful diction. Therefore, this study aims to reveal the meaning of the ecological lexicon in the form of flora and fauna in the novel “Al-Ajnihah al-Mutakassirah” using ecolinguistic studies. This study focuses on two aspects, namely: (1) The form of the lexicon of flora and fauna in the novel “Al-Ajnihah al-Mutakassirah” by Kahlil Gibran, (2) The meaning contained in the lexicon of flora and fauna in the novel “Al-Ajnihah al-Mutakassirah” by Kahlil Gibran. This type of research is descriptive qualitative research. This research produced some data, namely: (1) Lexicon flora and fauna in the novel “Al-Ajnihah al-Mutakassirah” based on an ecolinguistics perspective consisting of lexicons of flora in the form of past verbs, present verbs, conifers, monocot plants, dicot plants, development in plants, fauna lexicons in the form of present verbs, aves, mammals, reptiles, arthropods, and animal organs (2) The meaning of the lexicon of flora and fauna in the novel “Al-Ajnihah al-Mutakassirah” by Kahlil Gibran contextually can be divided into 2, namely connotative and denotative. In addition, each lexicon also has its meaning for the Lebanese people.